Comparative evaluation of effectiveness of calibrated inter-dental brushes in maintaining oral hygiene and periodontal health: a randomized controlled clinical trial - Hugar, Shweta S.; Sureshbabu, Abhirami; Misra, Tanay; Kumbhojkar, Vinayak (International Journal Of Community Medicine And Public Health, 2023)
Background: Effective oral hygiene is a crucial factor in maintaining good oral health, which is associated with overall health and health-related quality of life. The control of biofilm is the common pillar of the prevention and control of periodontal disease. The interdental brush (IDB) currently represents the primary and most effective method available for interproximal cleaning compared with brushing alone or the combined use of tooth brushing and dental floss. Methods: A total of 40 participants, with 10 each in control and test group, participated in the study. Clinical examination of gingival index, full mouth bleeding scores and plaque index were recorded supra gingival scaling was performed. Test group- interdental brushes were given and oral hygiene instructions were given through Touch-to Teach method (TOP). At 4 week and 6 week follow up oral hygiene instructions were repeated to respective groups. After 3 months, clinical examination was done and exit survey on patient-reported outcome measures was administered. Results: Intergroup comparison of gingival index, plaque index and pocket probing depth showed statistically significant difference between test and control group. Conclusions: Within the limitations of the study, we concluded that the appropriate use of interdental brushes along with effective oral hygiene maintenance using TOP permitted proper cleaning of the area with a significant reduction in plaque and gingivitis.